Covid-19 pandemic implications for food and nutrition security in Brazil - Ribeiro-Silva, Rita de Cássia; Pereira, Marcos; Campello, Tereza; Aragão, Érica; Guimarães, Jane Mary de Medeiros; Ferreira, Andréa Jf; Barreto, Maurício Lima; Santos, Sandra Maria Chaves Dos (Ciência & saude coletiva, 2020)
The emergence of COVID-19 in Brazil further explained the massive discrepancy between different social realities coexisting in the country, rekindling the discussions about food and nutrition security, similarly to what has been happening in other countries facing the same pandemic situation. In this paper, we argue that the risks to hunger and food security in Brazil have been present since 2016 and are now being exacerbated due to the emergence of the COVID-19 epidemic. This situation requires knowing the extent and magnitude of the issue and articulation of measures in the three governmental spheres(federal, municipal and state) to ensure access to adequate and healthy food and reduce the disease's adverse effectson the diet, health, and nutrition among the most vulnerable people. Thus, this work aims to contribute to the debate on the measures to be adopted by governments and society to promote and ensure food and nutrition security and prevent insecurity and the expansion of hunger during and after the social and health crisis created by the pandemic.